CULTURAL DIVERSITY IN BILINGUAL EDUCATION - Desy Rusmawaty (Kantor Bahasa Kalimantan Timur, 2020)
AbstractBilingual education needs to consider the cultural diversity both on its content and delivery in two languages. The use of mother tongue can facilitate the learners to understand the concept of scientific terms used in other languages. It is noted that bilingual learners are able to develop their metalinguistic skills. They have flexibility in their thinking to process the understanding of words through two different languages. Therefore, this study aims to clarify the concept of language learning integrated to the content. Eurydice presented a concept that there should be a special teaching approach that brought out the learning of non-language subjects taught by and through foreign language.Keywords: bilingual education, cultural diversity, metalinguistic AbstrakPendidikan bilingual harus mempertimbangkan keberagaman budaya pada materi dan cara penyampaiannya dengan menggunakan dua bahasa. Penggunaan bahasa ibu dapat memfasilitasi pembelajar untuk mengerti konsep-konsep ilmiah yang digunakan dalam bahasa lain. Hal yang perlu diperhatikan bahwa pembelajarbilingual mampu mengembangkan kemampuan metalinguistik mereka. Mereka memiliki fleksibilitas untuk memahami kata dalam dua bahasa yang berbeda. Oleh karena itu, studi ini dilakukan untuk mengklarifikasi konsep dari pembelajaran bahasa yang berintegrasi dengan pembelajaran materi lain (konten). Eurydicemengenalkan konsep bahwa perlu adanya pendekatan pengajaran khusus yang menekankan pada pembelajaran subjek non-bahasa yang diajarkan dengan dan melalui bahasa asing.Kata Kunci: pendidikan bilingual, keberagaman budaya, metalinguistik